PENGARUH PENERAPAN ORIENTASI LAYANAN PELANGGAN DAN MOTIVASI PELAYANAN PUBLIK TERHADAP KINERJA PEGAWAI BIDANG KESEHATAN LINGKUNGAN (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
The concept of New Public Management (New Public Management) includes the Application of Public Service Motivation or what is known as Public Service Motivation (PSM) and customer service orientation or Customer Service Orientation (CSO) including in the Central Government and local governments in Indonesia. Therefore, this study focuses on the application of the Environmental Health Sector in the Health Office of the South Tangerang City Government, Indonesia. Based on recent developments, research on customer service orientation and public service motivation on the performance of civil servants in public service work units in Tangerang Selatan City, Indonesia has never been carried out, this is the main reason why this quantitative study was carried out. The sample in this study was 56 civil servants who worked in the field of public services in their respective work units. This type of research includes quantitative research using the Onion Research Method, and the SEM-PLS (Structural Equation Modeling - Partial Least Square) model. This study shows that there are 12 dimensions containing customer service orientation variables, public service motivation variables and civil servant performance variables. The results of the study indicate that the Customer Service Orientation has a positive and significant influence on the performance of civil servants. Second, Customer Service Orientation has a positive and significant influence on Public Service Motivation. Third, Public Service Motivation has a positive and significant influence on the performance of civil servants. Customer Service Orientation has an indirect and significant effect on the performance of civil servants through the variable of public service motivation as a mediating variable. Effect of Total Relationship between Customer Service Orientation and Performance of Civil Servants with Public Service Motivation as a mediating variable: shows that the total relationship is a Partial Mediation relationship.